IMPLEMENTASI PERATURAN PRESIDEN NOMOR 87 TAHUN 2016 TENTANG SATUAN TUGAS SAPU BERSIH PUNGUTAN LIAR DI PROVINSI JAWA TIMUR - Helmi Perdana Putra (DIA: Jurnal Administrasi Publik, 2019)
ABSTRACTThe rise of illegal levies that occur in Indonesia has damaged the joint life of society, nation and state. On October 20, 2016, the President issued Peraturan Presiden Nomor 87 Tahun 2016 concerning the Wild Sweeping Clean Sweep Task Force by appointing the Coordinating Minister for Political, Legal and Security Affairs to control and be responsible for the activities of the Wild Sweeping Clean Sweep Task Force. How is Peraturan Presiden Nomor 87 Tahun 2016 concerning the Clean Sweeping Task Force Task Force implemented? What is the Policy Model for the Wild Sweeping Task Force Clean Sweep Task Force? The focus of this research analysis is that good governance actors consist of, first, the state, which is elaborated in the executive, legislative and judiciary branches and the military. Second, civil society, consisting of NGOs, mass organizations, mass media, associations based on professionalism, religious groups and others. And third, economic markets. The three actors of good governance interact with each other and influence each other according to their respective capacities. Analyzed from Peraturan Presiden Nomor 87 Tahun 2016 concerning the Clean Sweeping Task Force on Wild Levies, Policy of East Java Governor Surat Keputusan Gubernur Jawa Timur No. 188/624/kpts/013/2016 concerning the Establishment of the Wild Sweeping Clean Sweep Task Force in East Java and the Guiding Factors for Target, Communication, Resources, Disposition, Bureaucratic Structure, Characteristics of Implementing Institutions, Social, Economic and Political Conditions. The research findings obtained that since the implementation of the activities of the eradication of the Provincial/Regency/City extortion unit up to September 12, 2018, a total of 712 cases were obtained, for law enforcement in the form of arrest operations of 228 suspected suspects, and from both provincial, district , and the City as many as 133 people were caught in the operation caught red-handed.